(untitled) (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2025)
ABSTRACT Sharia shares are an investment instrument that has market opportunities and quite large development potential in Indonesia because it is a country with the largest Muslim population in the world. This research analyzes financial distress and its influence on financial ratios on sharia stocks in Indonesia. The proxy used in calculating financial distress is using the Modified Altman Z-Score formula and financial ratios consist of liquidity ratios, namely using the Current Ratio (CR), solvency ratios, namely Debt to Total Assets Ratio (DAR), profitability ratios, namely Earning Per Share (EPS). The samples in this research were companies listed on the sharia index, namely the Jakarta Islamic Index 70 (JII70) using a purposive sampling technique. From a total population of 70 companies, 14 companies were selected with a research duration of 10 years from 2015-2024. This research uses panel data regression analysis. The results of this research are that there is a positive and significant influence of financial distress (Z-Score value) and profitability ratio (EPS value) on sharia stock prices. Meanwhile, liquidity (CR value) and solvency ratio (DAR value) have an insignificant influence on sharia stock prices. The independent variables simultaneously have a significant effect on sharia stock prices with an R2 value of 88.16 percent.